Additive-free coupling of bromoalkynes with secondary phosphine oxides to generate alkynylphosphine oxides in acetic anhydride. Issue 6 (27th January 2020) - Ruan, Hongjie; Meng, Ling-Guo; Xu, Hailong; Liang, Yuqing; Wang, Lei
Abstract : A coupling of bromoalkynes with secondary phosphine oxides was developed to generate alkynylphosphine oxides under additive-free conditions in acetic anhydride. Abstract : A coupling of bromoalkynes with secondary phosphine oxides was developed for the synthesis of alkynylphosphine oxides. This transformation was accomplished under additive-free conditions in acetic anhydride (Ac2 O). The reaction could be carried out under mild conditions, and a wide range of secondary phosphine oxides were obtained in good yields.